UPAYA MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK DENGAN TEKNIK SOSIODRAMA DI SMP - Ningsis, Lidya; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEvery individual will requires confidence every day in various ways, including students in following the teaching and learning process in school. The good level of confidence is making good decision and easy to have a new friend, good relationships, and help individuals maintain the success. A common problem in this research is "How increasing students? confidence with socio-drama techniques in the classroom VIII SMP Negeri 22 Pontianak in 2019?". The method in this research was descriptive method. Based on the results, before socio-drama was 61% it means, in the medium category and after it was given socio-drama technique is 90% with a high category. It can be concluded that socio-drama technique to increase student confidence class VIII SMP Negeri 22 Pontianak was good. The suggestions (1) Teacher Guidance and Counseling is expected to improve the process of implementing Engineering Socio-drama by carrying out the Socio-drama Technique two or three times in one semester. (2) Students are expected to be more active and more confident in the implementation of the Socio-drama Technique. (3) For researchers is expected to be able to make students more explore the role being played by students participating in the Socio-drama Engineering activities. Keywords : Socio-Drama Technique, Self-Confidence